The Influence of Service Quality on Cooperative Member Satisfaction in Mondang Village, Sayur Matinggi District - Ahmad Sayuti Pulungan; Makhrani Makhrani (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
This study aims to determine the effect of service quality on satisfaction of cooperative members in Mondang village, Sayur Matinggi sub-district regarding service quality based on respondents' responses obtained from a questionnaire of 17 items with a total of 62 respondents. Data description analysis intended in this study includes calculating the mean or average ( M), median (Me), and mode (Mo). Based on the results of this study, there is a positive and significant influence of service quality variables on member satisfaction variables. Based on the results of this study, it was revealed that most members thought that service quality was categorized as sufficient with a percentage of 53%. Based on the research results, the mean of service quality is 48.53 and it can be said that service quality is in sufficient condition. The R value of 0.453 indicates that the variance in the cooperative member satisfaction variable can be explained by the service quality variable of 45.3%. The second hypothesis is accepted, namely service quality has a positive and significant effect on member satisfaction. This is indicated by a positive line coefficient value and a significance value of less than 0.05.